2023
DOI: 10.1177/08968608231172740
|View full text |Cite
|
Sign up to set email alerts
|

ISPD Catheter-related Infection Recommendations: 2023 Update

Abstract: Peritoneal dialysis (PD) catheter-related infections are important risk factors for catheter loss and peritonitis. The 2023 updated recommendations have revised and clarified definitions and classifications of exit site infection and tunnel infection. A new target for the overall exit site infection rate should be no more than 0.40 episodes per year at risk. The recommendation about topical antibiotic cream or ointment to catheter exit site has been downgraded. New recommendations include clarified suggestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 138 publications
(281 reference statements)
0
20
0
1
Order By: Relevance
“…36 ISPD guidelines recommend that prophylactic antibiotics should be administered immediately before catheter placement to prevent catheter-related infections. 32 In the present study, prophylactic antibiotics were administered in most cases. DM is widely recognised as a risk factor for post-surgical infections.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…36 ISPD guidelines recommend that prophylactic antibiotics should be administered immediately before catheter placement to prevent catheter-related infections. 32 In the present study, prophylactic antibiotics were administered in most cases. DM is widely recognised as a risk factor for post-surgical infections.…”
Section: Discussionmentioning
confidence: 93%
“…Although the 2023 ISPD guidelines for catheter-related infections have downgraded the recommendation, the guideline still recommended daily topical application of antibiotic cream or ointment to the catheter exit site. 32 However, an international, prospective, observational study found that daily topical application of antibiotic cream or ointment to the catheter exit site has not been implemented in Japan. 33 In fact, the Japanese PD guidelines suggest not applying mupirocin/gentamicin ointment to the exit sites of PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…1. clinical features consistent with peritonitis (i.e., abdominal pain and/or cloudy dialysis effluent); 2. dialysis effluent white cell count .100/ml or .0.1310 9 /L (after a dwell time of at least 2 hours), with .50% polymorphonuclear leukocytes; and 3. positive dialysis effluent culture.…”
Section: Definitionsmentioning
confidence: 99%
“…We commend Chow et al on publishing these International Society for Peritoneal Dialysis (ISPD) Guidelines on PD Catheter-related Infections, a welcome update to the 2017 Guidelines. 1 These updated Guidelines have modified definitions of tunnel infection, made recommendations regarding cause-specific catheter-related infection, set a new target for exit-site infection rate and discuss suggestions about the need for an exit-site dressing cover.…”
mentioning
confidence: 99%